Genetic and Antigenic Characteristics of Highly Pathogenic Avian Influenza A(H5N8) Viruses Circulating in Domestic Poultry in Egypt, 2017–2021 - Kandeil, Ahmed; Moatasim, Yassmin; El Taweel, Ahmed; El Sayes, Mohamed; Rubrum, Adam; Jeevan, Trushar; McKenzie, Pamela P.; Webby, Richard J.; Ali, Mohamed A.; Kayali, Ghazi; El-Shesheny, Rabeh (Microorganisms (Basel), 2022)
In Egypt, the endemicity of avian influenza viruses is a serious concern. Since 2016, several outbreaks of H5N8 have been recorded among domestic poultry in various areas of the country. Active surveillance of domestic poultry across several governorates in Egypt from 2017 to 2021 detected at least six genotypes of Highly Pathogenic Avian Influenza (HPAI) H5N8 viruses with evidence of partial or complete annual replacement of dominant strains. Although all Egyptian H5N8 viruses had clade 2.3.4.4b hemagglutinin (HA) genes, the remaining viral gene segments were from multiple geographic origins, indicating that the H5N8 isolates resulted from multiple introductions. Mutations in the viral proteins associated with pathogenicity and antiviral drug resistance were detected. Some mutations in the HA resulted in antigenic drift. Heterogeneity in circulating H5N8 HPAI threatens poultry production and public health.